Fashion - Lehnert, Gertrud (Hauppauge, N.Y. : Barron's Educational Series, 1998)
Traces the history of fashion from its beginnings in ancient civilizations through the twentieth century, identifying important trends, and discussing the role of fashion in culture throughout the world.
Translated from the German.
Includes bibliographical references (p. 185) and index.
Reference and Research Book News.
Young Adult
Keywords: Clothing and dress -- History; Fashion -- History; Clothing and dress -- History; Fashion -- History